A fast electrochemical quartz crystal microbalance (EQCM) evidences the presence of nanobubbles in alkaline water splitting - Leppin, Christian; Langhoff, Arne; Johannsmann, Diethelm (Physical Chemistry Chemical Physics)
Nanobubbles in water splitting are recognized by the EQCM-D. They are ubiquitous. Lifetimes are in the range of seconds.

Charge transfer in superbase n-type doping of PCBM induced by deprotonation - Dong, Chuan-Ding; Bauch, Fabian; Hu, Yuanyuan; Schumacher, Stefan (Physical Chemistry Chemical Physics)
Charge transfer mechanism in the deprotonation-induced n-type doping of PCBM.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Charge transfer in superbase n-type doping of PCBM induced by deprotonation - Dong, Chuan-Ding; Bauch, Fabian; Hu, Yuanyuan; Schumacher, Stefan (Physical Chemistry Chemical Physics)
Charge transfer mechanism in the deprotonation-induced n-type doping of PCBM.

Threshold photoelectron spectroscopy and dissociative photoionization of benzonitrile - Kamer, Jerry; Schleier, Domenik; Donker, Merel; Hemberger, Patrick; Bodi, Andras; Bouwman, Jordy (Physical Chemistry Chemical Physics)
The seven parallel dissociative ionization channels of benzonitrile yield highly stable fragment ions with commensurate abundance, underlining the potential role of the benzonitrile cation as hub species in the interstellar medium.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Threshold photoelectron spectroscopy of trimethylborane and its pyrolysis products - Schleier, Domenik; Gerlach, Marius; Schaffner, Dorothee; Mukhopadhyay, Deb Pratim; Hemberger, Patrick; Fischer, Ingo (Physical Chemistry Chemical Physics)
A new decomposition mechanism for trimethylborane at high temperatures has been discovered.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Measurement and modelling solubility of amino acids and peptides in aqueous 2-propanol solutions - Do, Hoang Tam; Franke, Patrick; Volpert, Sophia; Klinksiek, Marcel; Thome, Max; Held, Christoph (Physical Chemistry Chemical Physics)
In this work the solubility of 15 amino acids and 18 peptides in aqueous 2-propanol solutions was successfully modelled using PC-SAFT that used recently determined experimental melting properties as input data.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Thermostable water reservoirs in the interlayer space of a sodium hectorite clay through the intercalation of γ-aminopropyl(dimethyl)ethoxysilane in toluene - Keil, Waldemar; Zhao, Kai; Oswald, Arthur; Bremser, Wolfgang; Schmidt, Claudia; Hintze-Bruening, Horst (Physical Chemistry Chemical Physics)
Thermostable compartmentalized sodium-water sites through intercalated γ-aminopropyl-dimethyl-ethoxy silane in synthetic hectorite.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Diffusion of the carbon dioxide–ethanol mixture in the extended critical region - Chatwell, René Spencer; Guevara-Carrion, Gabriela; Gaponenko, Yuri; Shevtsova, Valentina; Vrabec, Jadran (Physical Chemistry Chemical Physics)
The effect of traces of ethanol in supercritical carbon dioxide on the mixture's thermodynamic properties is studied by molecular simulations and Taylor dispersion measurements.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Recombination mechanisms of luminescence type gas sensors - Poeplau, Michael; Ester, Stephan; Henning, Bernd; Wagner, Thorsten (Physical Chemistry Chemical Physics)
The impact of the recombination mechanisms in luminescent materials is discussed with regard to luminescence based gas-sensing applications and the use of semiconducting materials, as an alternative to organic–metal complexes, is outlined.

In silico investigation of Cu(In,Ga)Se2-based solar cells - Mirhosseini, Hossein; Kormath Madam Raghupathy, Ramya; Sahoo, Sudhir K.; Wiebeler, Hendrik; Chugh, Manjusha; Kühne, Thomas D. (Physical Chemistry Chemical Physics)
State-of-the-art methods in materials science such as artificial intelligence and data-driven techniques advance the investigation of photovoltaic materials.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Tumbling with a limp: local asymmetry in water's hydrogen bond network and its consequences - Elgabarty, Hossam; Kühne, Thomas (Physical Chemistry Chemical Physics)
Ab initio molecular dynamics simulations of ambient liquid water and energy decomposition analysis have recently shown that water molecules exhibit significant asymmetry between the strengths of the two donor and/or the two acceptor interactions.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Electron paramagnetic resonance study of ferroelectric phase transition and dynamic effects in a Mn2+ doped [NH4][Zn(HCOO)3] hybrid formate framework - Navickas, Marius; Giriūnas, Laisvydas; Kalendra, Vidmantas; Biktagirov, Timur; Gerstmann, Uwe; Schmidt, Wolf Gero; Mączka, Mirosław; Pöppl, Andreas; Banys, Jūras; Šimėnas, Mantas (Physical Chemistry Chemical Physics)
EPR spectroscopy reveals the universality class and dynamic effects of the [NH4][Zn(HCOO)3] hybrid formate framework.

Chemistry of iron nitrate-based precursor solutions for spray-flame synthesis - Stodt, Malte F. B.; Gonchikzhapov, Munko; Kasper, Tina; Fritsching, Udo; Kiefer, Johannes (Physical Chemistry Chemical Physics)
Understanding the chemistry of precursor solutions for spray-flame synthesis is a key step to developing inexpensive and large scale applications for tailored nanoparticles.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Structural dynamics upon photoexcitation-induced charge transfer in a dicopper(i)–disulfide complex - Naumova, Maria; Khakhulin, Dmitry; Rebarz, Mateusz; Rohrmüller, Martin; Dicke, Benjamin; Biednov, Mykola; Britz, Alexander; Espinoza, Shirly; Grimm-Lebsanft, Benjamin; Kloz, Miroslav; Kretzschmar, Norman; Neuba, Adam; et al. (Physical Chemistry Chemical Physics)
A study of structural evolution upon photoinduced charge transfer in a dicopper complex with biologically relevant sulfur coordination.

Structural heterogeneity in a parent ground-state structure of AnPixJg2 revealed by theory and spectroscopy - Scarbath-Evers, Laura Katharina; Jähnigen, Sascha; Elgabarty, Hossam; Song, Chen; Narikawa, Rei; Matysik, Jörg; Sebastiani, Daniel (Physical Chemistry Chemical Physics)
Extensive molecular dynamics simulations reveal two distinct isoforms of the cyanobacteriochrome AnPixJg2 (in its Pr state) with different chromophore conformations, yielding implications for spectroscopic properties.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Kinetics of ozone decomposition in porous In2O3 monoliths - Klawinski, Danielle; Weinberger, Christian; Klaus, Dominik; Smått, Jan-Henrik; Tiemann, Michael; Wagner, Thorsten (Physical Chemistry Chemical Physics)
We determine ozone decomposition on indium oxide by utilizing the gas transducing properties of hierarchically porous monoliths.

Analysis of dispersive interactions at polymer/TiAlN interfaces by means of dynamic force spectroscopy - Wiesing, M.; de los Arcos de Pedro, Maria Teresa; Gebhard, M.; Devi, A.; Grundmeier, Guido (Physical Chemistry Chemical Physics)
Dispersion forces due to polarizable subsurface layers govern TiAlN/polymer interactions and decrease by 50% when oxidizing TiAlN to form TiAlO.

Reline aqueous solutions behaving as liquid mixtures of H-bonded co-solvents: microphase segregation and formation of co-continuous structures as indicated by Brillouin and 1H NMR spectroscopies - Posada, E.; Lopez Salas, Nieves; Jiménez Riobóo, R. J.; Ferrer, M. L.; Gutiérrez, M. C.; del Monte, F. (Physical Chemistry Chemical Physics)
Deep eutectic solvents (DESs) offer a suitable alternative to conventional solvents in terms of both performance and cost-effectiveness.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Surface induced vibrational modes in the fluorescence spectra of PTCDA adsorbed on the KCl(100) and NaCl(100) surfaces - Paulheim, A.; Marquardt, C.; Sokolowski, M.; Hochheim, M.; Bredow, T.; Aldahhak, Hazem; Rauls, E.; Schmidt, Wolf Gero (Physical Chemistry Chemical Physics)
We report a combined experiment-theory study on low energy vibrational modes in fluorescence spectra of perylene-3,4,9,10-tetracarboxylic acid dianhydride (PTCDA) molecules.

Surface induced vibrational modes in the fluorescence spectra of PTCDA adsorbed on the KCl(100) and NaCl(100) surfaces - Paulheim, A.; Marquardt, C.; Sokolowski, M.; Hochheim, M.; Bredow, T.; Aldahhak, Hazem; Rauls, E.; Schmidt, Wolf Gero (Physical Chemistry Chemical Physics)
We report a combined experiment-theory study on low energy vibrational modes in fluorescence spectra of perylene-3,4,9,10-tetracarboxylic acid dianhydride (PTCDA) molecules.